2005
DOI: 10.1016/j.vetmic.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo susceptibility of the honeybee bacterial pathogen Paenibacillus larvae subsp. larvae to the antibiotic tylosin

Abstract: The minimal inhibitory concentrations (MICs) of tylosin were determined to 67 strains of Paenibacillus larvae subsp. larvae, the causal agent of American Foulbrood (AFB) disease, from different geographical origins. MIC values obtained ranged from 0.0078 to 0.5 mg/ml. These very low values imply that no resistance to tylosin was found in any isolate of the Foulbrood pathogen.The measurement of diseased larvae with AFB-clinical symptoms in three different field studies demonstrated that tylosin treatment could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Indeed, the accumulation of this antibiotic in honey has been determined in several studies [5][6][7]. However, tetracycline resistant strains have been identified in the USA, Canada and Argentina [8][9][10][11][12][13], and so other antibiotics, such as tylosin and lincomycin have also been proposed to control AFB [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the accumulation of this antibiotic in honey has been determined in several studies [5][6][7]. However, tetracycline resistant strains have been identified in the USA, Canada and Argentina [8][9][10][11][12][13], and so other antibiotics, such as tylosin and lincomycin have also been proposed to control AFB [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the concentrations of tylosin in the YLs indicated that although both forms of delivery -via paper pack or by dustinghad proven effective in controlling AFB in previous field trails (Hitchcock et al, 1970;Peng et al, 1996;Alippi et al, 2005;Reynaldi et al, 2010b), the more rapid elimination of tylosin applied by paper pack made this treatment the better one. The more time a microorganism spends at sub-inhibitory concentrations, the greater the chances of selection for a resistant microorganism.…”
Section: Resultsmentioning
confidence: 96%
“…Among them, tylosin appeared as an attractive alternative exhibiting both a bactericidal effect and the best in vitro inhibition of P. larvae in terms of the MIC, MBC, and MBC/MIC values (Peng et al, 1996;Alippi et al, 2005;Reynaldi et al, 2010b). Furthermore, the field efficacy of tylosin had already been demonstrated by several authors (Elzen et al, 2002;Alippi et al, 2005;Pettis & Feldlaufer, 2005). However, the consumption of tylosin was a trouble, for this reason, Peng et al (1996) recommended the use of cherry jelly as an attractant to improve the palatability of tylosin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations